Smoking-diseases correlation database: comprehensive analysis of the correlation between smoking and 422 diseases based on NHANES 2013–2018 - Chen, Xi; Wang, Tengkun; Tian, Yushan; Ma, Yinchao; Liu, Yuan; Chen, Huan; Hou, Hongwei; Hu, Qingyuan; Chu, Ming (Frontiers in Public Health, 2024)
Background: Smoking is a risk factor for a wide range of diseases. Previous research has confirmed over 30 Smoking-Associated Diseases in diverse systems. There is limited research exploring the correlation among multiple diseases, with an absence of comprehensive investigations. Few studies concentrate on diseases exhibiting a negative correlation with smoking, wherein smokers demonstrate a lower prevalence.Objective: This study aimed to detect the correlation between smoking and other diseases using data from NHANES and construct a Smoking-Diseases Correlation Database (SDCD). The second aim is to obtain an extensive screening test for diseases that may be linked to smoking.Methods: 39, 126 subjects' data from the National Health and Nutrition Examination Surveys (NHANES) 2013-2018 dataset was extracted. The baseline information, difference in blood routine and blood chemistry indicators between smokers and non-smokers, and diseases' correlation with smoking in four different models were analyzed by R. The data and statistics were aggregated into an online SDCD.Results: Our study reported 46 Smoking-Associated Diseases (SAD), including 29 Smoking Positively Associated Diseases (SPAD) and 17 Smoking Negatively Associated Diseases (SNAD). The SDCD of 422 diseases was constructed and can be accessed at https://chatgptmodel.shinyapps.io/sdcd/.Our findings revealed 46 SADs including 29 SPADs and 17 SNADs. We aggregated the statistics and developed online SDCD, advancing our understanding of the correlation between smoking and diseases.